2016
DOI: 10.1080/02699931.2016.1188059
|View full text |Cite
|
Sign up to set email alerts
|

Affect in the eyes: explicit and implicit evaluations

Abstract: The present study investigated whether another individual's gaze direction influences an observer's affective responses. In Experiment 1, subjective self-ratings and an affective priming paradigm were employed to examine how participants explicitly and implicitly, respectively, evaluated the affective valence of direct gaze, averted gaze, and closed eyes. The explicit self-ratings showed that participants evaluated closed eyes more positively than direct gaze. However, the implicit priming task showed an inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 68 publications
9
34
0
Order By: Relevance
“…Thus, unlike in the study by Lawson (2015), in this study, participants’ attention was not directed to the gaze direction, and concepts related to the stimulus face’s focus of attention were not activated. The results by Chen et al (2017a) showed that the response (categorization) times for positive words were significantly shorter when they were presented after direct-gaze rather than closed-eyes primes, whereas the response times to negative words were significantly shorter when they were presented after closed-eyes rather than direct-gaze primes. For both targets, the response times after averted-gaze primes were numerically between those observed after direct-gaze and closed-eyes primes, but these response times did not differ statistically significantly from those.…”
Section: Behavioral Paradigms With Implicit Measuresmentioning
confidence: 89%
See 4 more Smart Citations
“…Thus, unlike in the study by Lawson (2015), in this study, participants’ attention was not directed to the gaze direction, and concepts related to the stimulus face’s focus of attention were not activated. The results by Chen et al (2017a) showed that the response (categorization) times for positive words were significantly shorter when they were presented after direct-gaze rather than closed-eyes primes, whereas the response times to negative words were significantly shorter when they were presented after closed-eyes rather than direct-gaze primes. For both targets, the response times after averted-gaze primes were numerically between those observed after direct-gaze and closed-eyes primes, but these response times did not differ statistically significantly from those.…”
Section: Behavioral Paradigms With Implicit Measuresmentioning
confidence: 89%
“…Thus, Chen et al (2017a) interpreted their results to indicate that seeing a direct gaze automatically activated more positive evaluations than did seeing closed eyes. Interestingly, Chen and colleagues also measured explicit affective feelings evoked by the stimuli.…”
Section: Behavioral Paradigms With Implicit Measuresmentioning
confidence: 99%
See 3 more Smart Citations